Evaluation of Thermal-Induced Polymorphic Transformation on Desloratadine and Desloratadine-Benzoic Acid Salt - Ahmad Ainurofiq; Rachmat Mauludin; Diky Mudhakir; Sundani Nurono Soewandhi (Tabriz University of Medical Sciences, 2020)
Background: Active pharmaceutical ingredients face a challenge in manufacturing due to adverse physicomechanical properties. Desloratadine (DES) form I exhibits poor mechanical behavior through the formation of capping during the tableting process. Salt formation from DES and benzoic acid (BA) has been observed to resolve poor mechanical properties. However, the ability to withstand heat from the manufacturing process should be implemented in DES and DES-BA salt. The aim of this study was to determine the differences between thermal treatment results on DES and DES-BA salt and whether it causes them to undergo polymorphic transformation. Methods: Salt was crystallized between DES and BA using the solvent evaporation method. DES and DES-BA salt were heated at 110°C, 159°C (melting point of DES), 181°C (melting point of DES-BA), and 190°C. Following this, characterization was performed using differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and solubility testing. Results: Polymorphic transformation caused by heat occurred in DES, but not in DES-BA salt. The transformation of DES was induced by the effect of heating, which changed polymorph I to a mixture of polymorph I and III at 110°C, to polymorph II at 159°C, and to a mixture of polymorph I, II, and III at 190°C. Under 190oC, DES-BA is still stable and did not undergo a polymorphic transformation. However, at 190oC, decomposition started to occur, which implied decreased solubility, which did not occur in DES. Conclusion: The heating process did not cause DES-BA salt to undergo a polymorphic transformation. However, it caused decomposition at 190oC. DES underwent a polymorphic transformation when exposed to the same condition without decomposition. This provided information to always pay attention to temperature during manufacturing processes that include DES or DES-BA salt to avoid physicochemical changes.